Living without Lymph Nodes - Martha C. Monroe; K. Roberts; Barbara F. Shea (EDIS)
FCS-8831, a 4-page fact sheet by M.C. Monroe, K. Roberts, and B.F. Shea, helps women understand why lymph nodes are important, why sometimes it is necessary to sacrifice them, and recommends measures women can take to prevent or minimize infection and lymphedema after surgery for breast cancer. Includes additional sources of information and acknowledgments. Published by the UF Department of Family Youth and Community Sciences, March 2009.